Discovery and development of singlenucleotide polymorphism markers for resistance to Striga gesnerioides in cowpea (Vigna unguiculata) - Ongom, P.O.; Fatokun, C.; Boukar, O. (Frontiers Media, 2025)
Introduction: The parasitic weed [Striga gesnerioides (Willd.) Vatke] is a principal biotic constraint to cowpea [Vigna unguiculata (L.) Walp.] production in West and Central Africa, causing severe yield reductions. Multiple races of S. gesnerioides exist across the cowpea-growing areas of the sub-region. Past efforts identified some resistant sources and race-specific genes underpinning Striga resistance, but deployment of associated markers in breeding is limited. Here, we utilized a 51K cowpea iSelect single-nucleotide polymorphisms (SNPs) to decipher genomic regions underlying Striga resistance and explore marker conversion and validation for easy deployment.